2017
DOI: 10.1177/1010539517717364
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychosocial and Educational Prenatal and Postnatal Care Interventions for Married Immigrant Women in Korea: Systematic Review and Meta-analysis

Abstract: The rapid influx of married immigrant women from low-income Asian countries is a concern in South Korea, Japan, and Taiwan. In South Korea, 1 in 10 couples includes a Korean man and a migrant woman, increasing the need for prenatal and postnatal care interventions. Studies published in English or Korean after 2000 were retrieved from 8 databases and reviewed via a systematic review and meta-analysis of the effectiveness of prenatal and postnatal psychosocial and educational interventions in Korea. Of 3583 reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This reveals that a strategy for restoring microbiota is needed, excluding remedial supplementation with probiotic microbes. Also, further studies using Korean infants will help to identify factors causing the relatively rapid restoration of early gut microbiota in CS infants, such as Korean postpartum services ( Kyung Kim et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This reveals that a strategy for restoring microbiota is needed, excluding remedial supplementation with probiotic microbes. Also, further studies using Korean infants will help to identify factors causing the relatively rapid restoration of early gut microbiota in CS infants, such as Korean postpartum services ( Kyung Kim et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interventions involving spousal participation reported greater effectiveness. 39 Two other studies in Iran on lifestyle and home care training showed improved lifestyle awareness and women’s performance in infant care. 11 , 40…”
Section: Discussionmentioning
confidence: 97%
“… 13 14 While in-depth explorations of specific programmes and interventions have been performed, there remains a paucity of knowledge regarding the scope and the outcomes measured by SRH migrant access interventions. 15 16 Moreover, the available evidence suggests that there are mixed effects of SRH interventions depending on the setting. Few studies to date have addressed the characteristics and range of SRH interventions for migrants, their underlying theory of change, reported outcomes and key enablers and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Reported effects at individual levels include active participation in the workplace and in income-generating activities, women empowerment, educational achievement and health systems outcomes such as reduced infant and maternal mortality 13 14. While in-depth explorations of specific programmes and interventions have been performed, there remains a paucity of knowledge regarding the scope and the outcomes measured by SRH migrant access interventions 15 16. Moreover, the available evidence suggests that there are mixed effects of SRH interventions depending on the setting.…”
Section: Introductionmentioning
confidence: 99%